SMOKING REGULATIONS FINAL RULE (Tufts Archival Research Center, 2007)
Final rule of General Services Administration smoking regulations. Provides background of health effects of secondhand smoke, goals of regulations, and full text of regulations. Indicates comments were considered. States that rule is not a "major rule", and therefore does not need a Regulatory Impact Analysis. Argues that benefits to society outweigh costs. Prohibits smoking in public places and defines creation of smoking areas.